The importance of creative problem solving: Reflections on my Master's thesis journey - Gishen, Roselyn M. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This Note from the Field is a reflection on the author’s journey through her Master’s thesis. Drawing on the concepts of pragmatism, creative thinking, and identity formation, this article details the non-linear nature of her research work and the unexpected learning opportunities and insights that arose along the way.